SUMATO Awning - Azhar, Izzatul Nadia; Mohamad Nizam, Fatin Nurdini; Omar, Mastura (2020)
Automated awning has been created and introduced to facilitate daily human activities. Various advantages such as the area will be maintained without the control of humans as well as save time. The main theme of this project is to prevent the clothesline or more focused on protecting the tables and chairs outside of a restaurant and the house's patio area. However, there is a shortage of existing inventions. Not all existing automated awning systems use raindrop and temperature sensors. Most can only be controlled manually. Thus, ‘Sumato Awning’ was introduced to address the problem. It is built from 2560 Arduino Mega, using the YL38 raindrop sensor and LM35 temperature, the awning can function itself. Then, the 16*2 LCD is used to display the motion and status of the awning operation. Among the other components used are buzzer to generate alarm sound, after the awning is fully flat, the LED will be lit to provide adequate lighting and water-mist fan for the consumer's comfort.